Edukasi Penyusunan Laporan Keuangan UMKM Burjo Minang Dan Jajanan Pasar Berkah Di Tamantirto - Muslim Algani; Ni Luh Gde Ana Pertiwi; Rochmad Bayu Utomo (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This service aims to increase knowledge of financial reports at Burjo Minang MSMEs and Berkah Market Snacks in Tamantirto through simple bookkeeping education and training. This research was conducted using qualitative methods and a descriptive approach. The research results show that simple bookkeeping training provides significant benefits for MSMEs in making accurate financial reports. This research also identifies factors that cause errors in bookkeeping and provides solutions to overcome these problems. Thus, this research contributes to increasing knowledge regarding financial reports and the effectiveness of bookkeeping at MSMEs Burjo Minang and Jajanan Pasar Berkah.